What Maintains the Metabolic Cost at Peak Anaerobic Test in Elite Young and Master Male Cyclists? - Sciamama-Saghiv, Moran (British Journal of Healthcare and Medical Research, 2023)
Purpose: The present study investigated the effect of aging on the oxygen utilization in healthy well-trained elite cyclists males young and masters at peak Wingate Anaerobic Test. Methods:Twenty young 21.21±1 and twenty masters 57.6±3.4 years were studied by Echocardiography performed with the subject sitting on a bicycle ergometry. Arterial oxygen was defined from echocardiographic measurements and venous oxygen content. Results: At peak Wingate Anaerobic Test, in young compare to masters, cardiac output (18.2±0.6 and 17.1±0.4 L•min-1 respectively), and stroke volume (84.0±5.0 and 78.2±6.1 mL respectively) were significantly (P < 0.05) higher, (a-v)O2 was significantly (P < 0.05) lower (122.5±2.9 and 126.1±3.1 mLO2 respectively) while %VO2 out of total energy utilized did not differ between groups. Conclusions: This study suggests that elite cyclist athlete young and masters respond to the Wingate Anaerobic Test by reducing their left ventricular systolic function in the face of increased afterload. The lack of differences at peak exercise in the oxygen utilization may be attributed to differences in energy metabolism, namely higher oxygen extraction in the masters, compensating for the lower oxygen delivery.